Zmiany natężenia transportu materiału zawieszonego w dolnym odcinku Obry - Młynarczyk, Zygmunt; Słowik, Marcin (Wydawnictwo Poznańskiego Towarzystwa Przyjaciół Nauk, 2007)
Research concerning changes of intensity of suspended load transport was done in the lower course of the Obra river near Miêdzyrzecz (Western Poland). Hydrological measurements were realized within 1 km long and 70–150 m wide section of the Obra river valley, which is situated about 3 km north-west of Miêdzyrzecz. Detailed analysis of relation between suspended sediment concentration and discharge afforded possibility for preliminary determining the way of suspended sediment supply to the river bed during high water stages. It was supposed that exposures of glacial and fluvioglacial sediments in high concave banks could be an important factor influencing the amount of delivery of suspended material. On the other hand, normal hysteretic loops (oriented clockwise) were observed in cross-sections 4 and 5. That fact would suggest that transported material originates form the Obra river bed or its nearest neighborhood. Besides, the process of sediment accretion was observed on the fragment of drowned floodplain during high water stages. This investigation allowed to illustrate the mechanism of forming floodplain sediments both at present and in the past. The problem of changes of amount of suspended load in longer time periods also was discussed. On the basis of measurement data and hydrological data from Miêdzyrzecz water-gauge, annual amount of suspended load was calculated for years 1971–1991. The main factor, which influenced the amount of sediment transport, was frequency of high water stages and hydraulic conditions of flow in the river bed. Flood events also were very important because of increased possibilities of suspended sediment supply from floodplain and steep bank slopes.